Breast Cancer: Making Sense of the Numbers - Martha C. Monroe; Barbara F. Shea; Linda B. Bobroff (EDIS, 2007)
FCS8825/FY895, a 5–page fact sheet by Martha C. Monroe, Barbara F. Shea, and Linda Bobroff, will help newly diagnosed breast cancer patients understand the numbers and statistics they will hear as they learn what type of cancer they have, what stage it is, and how aggressive it is. Includes explanations of the different scoring systems used by physicians and a section on understanding how treatments change survival odds. Published by the UF Department of Family, Youth and Community Sciences, December 2006.